Optimalisasi Intermediasi dan Pembiayaan BMT Menuju Pemberdayaan Ekonomi Masyarakat - Ulum, Fahrur (ISLAMICA: Jurnal Studi Keislaman, 2014)
This article seeks to discuss the economic empowerment of society through the optimalization of BMTâs function of intermediating and financing. Using a descriptive and qualitative approach, this article reveals that the success of economic empowerment should be supported by strategy, tactics and stepping. The program should also be implemented through segmentation and training of clients, providing human resources that understand the vision and mission of empowerment, optimizing BMTâs function of intermediating, and providing a coordinated tool of saving. Intermediation is conducted through developing economic potentials of Muslim community (ummah), improving the quality of human resources, mobilizing societal resources, bridging the relation between the rich and the poor and between the fund owners and users, coaching and balancing in terms of financial support.